The role of androgen receptors in atherosclerosis. (15th April 2018) - Takov, Kaloyan; Wu, Junxi; Denvir, Martin A.; Smith, Lee B.; Hadoke, Patrick W.F.
Abstract: Male disadvantage in cardiovascular health is well recognised. However, the influence of androgens on atherosclerosis, one of the major causes of many life-threatening cardiovascular events, is not well understood. With the dramatic increase in clinical prescription of testosterone in the past decade, concerns about the cardiovascular side-effects of androgen supplementation or androgen deprivation therapy are increasing. Potential atheroprotective effects of testosterone could be secondary to (aromatase-mediated) conversion into oestradiol or, alternatively, to direct activation of androgen receptors (AR). Recent development of animal models with cell-specific AR knockout has indicated a complex role for androgen action in atherosclerosis. Most studies suggest androgens are atheroprotective but the precise role of AR remains unclear. Increased use of AR knockout models should clarify the role of AR in atherogenesis and, thus, lead to exploitation of this pathway as a therapeutic target. Highlights: The influence of androgens on cardiovascular disease is not clear. This has implications for androgen replacement and androgen deprivation therapies. Use of (cell-specific) knockout models is helping clarify the influence of androgen-androgen receptor signalling in cardiovascular disease. Androgens may be atheroprotective but the importance of dose, duration of exposure and source is poorly understood. Understanding the link between androgens and atherosclerosis is key to improving androgen replacement/deprivation therapy.